Microfluidics and Nanofluidics : Theory and Selected Applications - Kleinstreuer, C. (Chichester : Wiley, 2014)
Fluidics originated as the description of pneumatic and hydraulic control systems, where fluids were employed (instead of electric currents) for signal transfer and processing. Microfluidics and Nanofluidics: Theory and Selected Applications offers an accessible, broad-based coverage of the basics through advanced applications of microfluidics and nanofluidics. It is essential reading for upper-level undergraduates and graduate students in engineering and professionals in industry.
Includes bibliographical references and index.
Print version record.
Keywords: Microfluidics; Nanofluids; SCIENCE -- Mechanics -- Fluids; TECHNOLOGY & ENGINEERING -- Engineering (General); Microfluidics; Nanofluids; Electronic books